Screening and Education of Intestinal Protozoa Infection in Elementary School-Age Children, Penjaringan District, North Jakarta: Skrining dan Edukasi Tentang Infeksi Protozoa Usus pada Anak Usia Sekolah Dasar, Kecamatan Penjaringan, Jakarta Utara - Kaisar, Maria Mardalena Martini; Muhyidin, Muhammad Fadli; Anggraini, Felicia; Wijaya, Meiliyana; Yolanda, Hanna; Surja, Sem Samuel; Kristin, Helen; Hengestu, Anastasia; Joprang, Freggy Spicano (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2024)
Urbanization in Jakarta has led to the development of slum settlements characterized by poor sanitation and limited access to clean water. This environment significantly increases the risk of intestinal protozoan parasitic infections (IPPIs), which are known to cause diarrhea and adversely affect the growth and development of children—key factors in the success of Indonesia's Emas 2045 initiative. To address this, the community service team from FKIK UNIKA Atma Jaya conducted a free fecal examination program for students at a public school in the Penjaringan District, a slum area in North Jakarta. The program included several phases: preparation, education, microscopic examination, and evaluation, involving both the school and the students' parents or guardians. Diagnostic methods utilized were direct examination and a modified Ziehl-Neelsen (ZN) staining technique. Out of 223 participants, 16.6% were found to be infected with IPPIs. The analysis revealed no significant correlation between infection rates and grade levels (p=0.106). This initiative is expected to enhance awareness among parents and students about IPPIs, leading to improved personal hygiene and sanitation practices. It also provides valuable data to authorities for assessing and formulating preventive policies against IPPIs